96 Development of the pardi (pica, arfid, rumination disorder interview): a structured assessment measure and diagnostic tool for feeding disorders. (4th October 2017) - Bryant-Waugh, R; Cooke, L
Abstract : Background: Feeding Disorders are poorly recognised and often go undiagnosed, yet the impact of accompanying inadequate nutrition and disruption to eating behaviour can be significant. Failure to identify and treat severe feeding problems may result in serious physical and mental health consequences and have negative effects on cognitive development and psychosocial functioning. Project: Over the past 3 years, members of the GOSH Feeding Disorders Team have led the development of a new assessment instrument designed to address a gap in available measures for feeding disorders. With collaborators in New York and Boston, the Team has developed the PARDI (Pica, ARFID (avoidant/restrictive food intake disorder), Rumination Disorder Interview), a structured clinical interview, with the aim of helping health professionals correctly diagnose and assess the severity of these disorders. Such a measure is vital for moving the field forward through facilitating the development of targeted interventions and improving the healthcare of those affected. This presentation will outline the process of the instrument's development, describing its structure and four parallel formats: parent version for 2–3 year-olds; parent version for children aged 4 and over; self-version for 8–13 year-olds; and self-version for those aged 14 and over. A diagnostic algorithm has been derived for the three diagnostic categories separately, as well as items assessing the severity of each disorder. The ARFID section contains three profile subscales allowing detailed assessment of key presenting features. Results: Preliminary results from our UK pilot study of the parent version of the measure will be presented. The PARDI was administered to parents/carers of over 50 patients attending the Feeding Disorders Service and feedback sought. Conclusion: Overall the measure was acceptable to participants, feasible to incorporate into routine assessment procedures, and the resulting diagnoses concurred with clinician judgement. The instrument is now being subjected to formal validation through a GOSHCC funded research study.